Performance Analysis of Preemptive Based Uniprocessor Scheduling - M Shanmugasundaram; R Kumar; Harish M Kittur (International Journal of Electrical and Computer Engineering (IJECE), 2016)
All the real-time systems are bound with response time constraints, or else, there is a risk of  severe consequences, which includes failure. The System will fail when not able to meet the requirements according to the specifications. The problem of real-time scheduling is very vast, ranging from uni-processor to complicated-multiprocessor. In this paper, we have compared the performance of real-time tasks that should be scheduled properly, to get optimum performance. Analysis methodology and the concept of optimization leads to the design of appropriate scheduling. We have done  the analysis among RM and EDF algorithm that are important for scheduling in uni-processor.